Balancing Faith and Rights: Addressing Abuse of Sharia-Based Inheritance Law In Non-Islamic Legal Systems - Masood Ahmed (QURU’: Journal of Family Law and Culture, 2026)
In India, Muslim Personal Law (Sharia-based) inheritance rules are frequently applied in social contexts that lack the ethical and institutional supports presumed in an ideal Islamic society. This gap facilitates the misuse of inheritance norms to the detriment of legally entitled yet socially vulnerable heirs—particularly women, elderly widows, and orphans—through the denial of shares, coercion, administrative obstruction, and the exploitation of guardianship arrangements and intra-family power asymmetries. The aim of this article is to examine the structure of Islamic inheritance in the Qur’an and Hadith, its implementation and disputes in Indian courts, and the legal, socio-economic impacts of its application in a non-Islamic system, including state interventions and community strategies to circumvent inheritance distributions. Employing a qualitative, descriptive design grounded in documentary and doctrinal analysis, the study synthesizes Qur’anic and Hadith provisions, selected contemporary references (including Saudi Arabia’s 2022 Family Law as a comparative articulation of farā’iḍ rules), and selected Indian judicial decisions and scholarly works to identify recurrent patterns of dispute, exploitation, and institutional response. The findings indicate that Islamic inheritance is often perceived as impractical under prevailing conditions because certain allocations may grant substantial shares to the deceased’s parents, while the widow and children who shoulder continuing livelihood needs may receive comparatively less. These parental shares may subsequently devolve to their heirs (including the deceased’s siblings), effectively shifting estate benefits to parties who may not assume responsibility for the surviving dependents. Indian courts therefore confront a dual mandate: applying Muslim personal law while delivering social justice amid heavy caseloads and persistent misuse of inheritance rules. This article recommends promoting reforms at both the community and state levels, with a focus on strengthening rights awareness, enforcing heirs’ obligations, protecting widows and orphans, improving administrative oversight, and developing Sharia-compliant mechanisms such as transparent hibah (inter vivos gifts), so that state intervention becomes a last resort.